Pendekatan Multimodal Terhadap Lanskap Linguistik: Tanda Larangan Di Kawasan Wisata Kyoto Jepang - Afifah, Muthi; Sugihartono, Sugihartono (Jurnal Sasindo UNPAM, 2025)
This study examines prohibition signs in Kyoto City tourist areas using Brown and Levinson’s (1987) politeness theory and the Linguistic Landscape framework (Backhaus, 2006). Prohibition signs, though one way communication, carry high potential for Face Threatening Acts (FTA). Kyoto’s cultural context adds layers of meaning, where signage reflects not only function but also aesthetics and local values. A total of 52 signs from Gion Shopping Street and Yasaka Shrine were analyzed, focusing on kebahasaan and visual elements. The findings show a mix of polite and impolite expressions, shaped by signs, content, context, and target audience. Kyoto City signage policy, emphasizing simplicity and harmony, also influences expression choices, limiting bright colours. This study reveals how politeness in public signage is contextually constructed and highlights the role of cultural and spatial factors in shaping public communication.